Media literacy, Access and political participation among south African black youth: a study of north-west university, Mafikeng campus (2015)
"This study explores the extent of media access and literacy of the black students of the North-West University, Mafikeng Campus, and the impact of these factors on the students’ knowledge of and attitude towards politics. Through questionnaires and interview guides, data was obtained from 232 respondents and 22 interviewees, respectively. The Internet (n=211; 90.9%) is accessible to the students when they are on the university campus while television (n= 137; 59.1%) and radio (n=53; 22.8%) are accessible outside the university. The respondents’ knowledge of South African politics gained through the news media is significantly associated with their attitude to the nation’s politics (X2 = 9.900, df = 1, p< 0.005) and their readiness to participate in South African politics (X2 = 5.889, df = 1, p< 0.005). However, respondents demonstrated political apathy, which they attributed to bad leadership "